Integrated thin film Si fluorescence sensor coupled with a GaN microLED for microfluidic point-of-care testing. (19th December 2017) - Robbins, Hannah; Sumitomo, Keiko; Tsujimura, Noriyuki; Kamei, Toshihiro
Abstract: An integrated fluorescence sensor consisting of a SiO2 /Ta2 O5 multilayer optical interference filter and hydrogenated amorphous silicon (a-Si:H) pin photodiode was coupled with a GaN microLED to construct a compact fluorescence detection module for point-of-care microfluidic biochemical analysis. The combination of the small size of the GaN microLED and asymmetric microlens resulted in a focal spot diameter of the excitation light of approximately 200 µ m. The limit of detection of the sensor was as high as 36 nM for fluorescein solution flowing in a 100 µ m deep microfluidic channel because of the lack of directionality of the LED light. Nevertheless, we used the GaN microLED coupled with the a-Si:H fluorescence sensor to successfully detect fluorescence from a streptavidin R-phycoerythrin conjugate that bound to biotinylated antibody-coated microbeads trapped by the barrier in the microfluidic channel.